2011
DOI: 10.1162/ling_a_00041
|View full text |Cite
|
Sign up to set email alerts
|

Grounding Systematic Syncretism in Learning

Abstract: It is commonly assumed that patterns of syncretism in inflectional paradigms are restricted in some way. In this article, I show how such restrictions can reflect cognitive constraints on language learning. Namely, I construct a learning algorithm that is biased toward certain types of affix distributions in paradigms, thereby rendering them systematic. In developing this algorithm, I rely on the traditional notions of underspecification and blocking, but recast them in terms of learners' biases toward general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…The rise and fall of the L-shaped morphome patterns of natural vs. unnatural syncretism and formal modeling of the computational primitives that favor one system over another (e.g Bobaljik (2004), Pertsova (2011), Graf (2012), and in the case of the present paper, adopting the tack of creating closely-controlled experimental conditions in which native speakers must choose between one of two potential, non-existing candidates, or rate the well-formedness of unseen inflected forms of wug words.…”
Section: The Case For Autonomous Morphomesmentioning
confidence: 99%
“…The rise and fall of the L-shaped morphome patterns of natural vs. unnatural syncretism and formal modeling of the computational primitives that favor one system over another (e.g Bobaljik (2004), Pertsova (2011), Graf (2012), and in the case of the present paper, adopting the tack of creating closely-controlled experimental conditions in which native speakers must choose between one of two potential, non-existing candidates, or rate the well-formedness of unseen inflected forms of wug words.…”
Section: The Case For Autonomous Morphomesmentioning
confidence: 99%
“…For instance, most patterns of syncretism that cannot be captured by underspecification alone, can be captured by underspecification and blocking (Pertsova, 2011). There are also cross-paradigmatic regularities involving syncretism: in many cases, the same cells tend to be syncretic in different paradigms within the same language revealing that something systematic is going on.…”
Section: Challenges For Inflectional Learning Models: Ambiguity and Imentioning
confidence: 99%
“…According to the typological data by Baerman and Brown (2005) from the World Atlas of Language Structures, from a sample of 140 languages that mark subject and person agreement on the verbs, 80 (or 57%) have no syncretism or homonymy in any of the paradigms, which guarantees that every phonologically distinct form can be mapped to a single conjunction of features values. Other typological work on person number marking found that in paradigms with syncretism the most common type of syncretism is the one that can be described by underspecification (Cysouw, 2003;Pertsova, 2011), which is also a conjunctive type of syncretism.…”
Section: Conjunctive Biasmentioning
confidence: 99%
See 2 more Smart Citations